Deformation Mechanism and Control Technology of Surrounding Rock in the Deep-Buried Large-Span Chamber. (17th October 2020) - Yu, Weijian; Li, Ke
Abstract : The selection of the support scheme for deep-buried and large-span chambers has been a severe problem in underground engineering. To further study the mechanical mechanism of large deformation, based on the repair engineering of the chambers of Pingdingshan No.6 mine in China, the field investigation, laboratory test, numerical simulation, and theoretical analysis were studied. The surrounding rock of the central substation chamber (CSC) and the main pumping chamber (MPC) were classified according to the rock mass rating (RMR) classification method, and the main factors affecting the stability of the surrounding rock of the chambers were revealed. A prediction model of mechanical parameters of the surrounding rock was established based on the Hoek-Brown failure criterion. Additionally, the prediction results were used in FLAC 3D to further analyze the failure of the original support scheme, and the feasibility of the restoration plan was proposed. Six key points of support technology for this kind of chamber were put forward. Comprehensive support and repair scheme, including "bolt, metal mesh, shotcrete, grouting, anchor cable, and combined anchor cable, " was put forward. The engineering practice indicated that the deformation rate was less than 0.7 mm/d, which was beneficial to the long-term stability of CSC and MPC. The implementation of this restoration project can provide a reference for other similar projects.